Correlation investigation of odour-profile and temperature intensity - Ali Ibrahim, Muhammad Naqiuddin; Najib, M. S.; Mohd Daud, Suhaimi (Penerbit UMP, 2022)
Water is important to all human and economic activity. Despite its abundant water resources, Malaysia's water demand and consumption was increased in recent years. This study had been investigating the condition of Malaysia's water resources at present. This study aims to identify water by examining its odour profile and temperature intensity. E-Anfun E-nose was applied to generate a pattern of the volatile compounds included in the samples. The optimal correlation was discovered between odour feature extractions from many samples produced using the same E-Anfun unit. An intelligent algorithm namely Case-Based Reasoning (CBR) was employed to detect the odour of different national standard tap water samples. CBR has produced measurable performance of 100% classification rate of accuracy